2003
DOI: 10.1007/s00232-003-0624-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Properties of Bacillus thuringiensis Insecticidal Toxins Using a Potential-sensitive Fluorescent Probe

Abstract: A potential-sensitive fluorescent probe, 3,3'-dipropylthiadicarbocyanine iodide, was used to analyze, at pH 7.5 and 10.5, the effects of Bacillus thuringiensis toxins on the membrane potential generated by the efflux of K(+) ions from brush border membrane vesicles purified from the midgut of the tobacco hornworm, Manduca sexta. Fluorescence levels were strongly influenced by the pH and ionic strength of the media. Therefore, characterization of the effects of the toxins was conducted at constant pH and ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…The response time of the measurement is short [12,13], and changes in fluorescence level are directly associated to changes in membrane potential induced by the changes in ionic flux. However, the use of this system to determine pore formation by Cry toxins has been questioned [15]. Here, we validated the use of diSC 3 (5), showing that under specific ionic conditions, where the surface membrane potential is shielded and the intrinsic permeability is inhibited, the ionic strength and osmolarity have no effects on the analysis of membrane potential of M. sexta membrane vesicles and changes in fluorescence can be correlated with ionic permeability induced by Cry toxins.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The response time of the measurement is short [12,13], and changes in fluorescence level are directly associated to changes in membrane potential induced by the changes in ionic flux. However, the use of this system to determine pore formation by Cry toxins has been questioned [15]. Here, we validated the use of diSC 3 (5), showing that under specific ionic conditions, where the surface membrane potential is shielded and the intrinsic permeability is inhibited, the ionic strength and osmolarity have no effects on the analysis of membrane potential of M. sexta membrane vesicles and changes in fluorescence can be correlated with ionic permeability induced by Cry toxins.…”
Section: Introductionmentioning
confidence: 75%
“…3A, B). A previous report from Kirouac et al [15] suggested that osmolarity and ionic strength have a dramatic effect on diSC 3 (5) dye sensibility and on the estimations of changes in membrane potential. It is important to mention that these authors did not take into account the effects that pH and ionic strength have on the surface potential.…”
Section: Cry1camentioning
confidence: 96%
See 1 more Smart Citation
“…The lower activity of Cry1Aa and Cry1Ab is rather surprising, in view not only of the in vivo toxicity but also of the previous in vitro studies. Cry1Aa, Cry1Ab, Cry1Ac, and Cry1Ea had similar pore-forming activities in brush border membrane vesicles, as observed using an osmotic-swelling assay (36) or a potential-sensitive fluorescent dye (17). The lower pore-forming ability estimated for Cry1Ca using the osmoticswelling assay (36) compared with that measured using the potential-sensitive dye (17) was explained by the effect of ionic strength on the activity of this toxin (11).…”
Section: Discussionmentioning
confidence: 70%
“…1) or from their ability to increase the permeability of vesicles prepared from this membrane (17,36). In the electrophysiological assay, the pore-forming ability of the toxins is measured in living cells in which the presence of a strong membrane potential, which is absent during the incubation of the vesicles with the toxin prior to the osmotic swelling (36) and the fluorescence assay (17), could influence pore formation. However, this possibility does not appear to be sufficient to explain why the relative toxicity and in vitro activity of the toxins do not follow a similar pattern.…”
Section: Discussionmentioning
confidence: 99%